Replacement Gastrostomy Tube Causing Acute Pancreatitis: Case Series with Review of Literature - Shah, Anish M; Shah, Nihar; DePasquale, Joseph R (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Percutaneous endoscopic gastrostomy (PEG) feedings are generally considered safe with few serious complications. Acute pancreatitis is a rare complication associated with replacement percutaneous endoscopic gastrostomy tubes. Case report We report two cases of acute pancreatitis induced by migrated replacement percutaneous endoscopic gastrostomy tubes. Conclusions Migration of a balloon into the duodenum can result in external manipulation of the ampulla of Vater thereby disturbing the flow of pancreatic secretions leading to acute pancreatitis. Recognition of this complication is important and should be included as potential etiology of acute pancreatitis in patients receiving percutaneous endoscopic gastrostomy feedings. Periodic examination and documentation of the distance of the balloon from the skin should be performed to document the position of the tubes or any inadvertent migration of the tubes. The use of Foley catheters as permanent replacement tubes should be considered medically inappropriate.